1987
DOI: 10.1002/cem.1180010105
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical foundation for the PLS algorithm

Abstract: SUMMARYPartial least squares (PLS) modeling is an algorithm for relating one or more dependent variables to two or more independent variables. As a regression procedure it apparently evolved from the method of principal components regression (PCR) using the NIPALS algorithm, which is similar to the power method for determining the eigenvectors and eigenvalues of a matrix. This paper presents a theoretical explanation of the PLS algorithm using singular value decomposition and the power method. The relation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
170
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(174 citation statements)
references
References 7 publications
1
170
0
3
Order By: Relevance
“…In PLSR, the original Xdata, are projected onto latent variables on which the regressions are performed. Further details about PLSR are given elsewhere [25][26][27]. Principal component analysis (PCA) was used to get a general overview over the structure in the data.…”
Section: Calculations and Error Estimatesmentioning
confidence: 99%
“…In PLSR, the original Xdata, are projected onto latent variables on which the regressions are performed. Further details about PLSR are given elsewhere [25][26][27]. Principal component analysis (PCA) was used to get a general overview over the structure in the data.…”
Section: Calculations and Error Estimatesmentioning
confidence: 99%
“…Multivariate calibration methods are well-known to play a very important role in the multicomponent analyses. [3][4][5][6] Partial least squares (PLS) regression as a full spectrum multivariate calibration method was originally developed by Wold 7 and chemically applied by Wold et al 8,9 It has been successfully applied to the quantitative analyses of spectroscopic 10,11 as well as electrochemical data. 12 The PLS methods are represented by two modifications, known as PLS-1 and PLS-2.…”
Section: Introductionmentioning
confidence: 99%
“…The NIR reflectance spectra of these solutions were measured from 1100 to 1700 nm. The PLS calibration model was constructed using these eight calibration mixtures in the range of 1100 to 1700 nm using three latent variables and MATLAB code written inhouse using the algorithm of Lorder et al 47 The resulting PLS calibration model was used to estimate the solid profiles shown in Figure 6 for comparison to the model estimated mass profiles. It should be emphasized that the reflectance R was used in the PLS calibration rather than the conventional quantity log(1/R), as the raw signal R gave the best linearity with the fewest number of factors.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%